A deterministic model for the inventory policy of countries for procurement of vaccines - Pinarbasi, Aysun; Vizvari, Bela (Springer, 2023)
The countries are the units that procure the vaccines during the COVID-19 pandemic. The delivered quantities are huge. The countries must bear the inventory holding cost according to the variation of stock quantities. This cost depends on the speed of the vaccination in the country. This speed is time-dependent. The vaccinated portion of the population can be approximated by the cumulative distribution function of the Cauchy distribution. A model is provided for determining the minimal-cost inventory policy and its optimality conditions are provided. The model is solved for 20 countries for different numbers of procurements. The results reveal the individual behavior of each country.
Keywords: COVID-19; Vaccination; Inventory policy; Invendory holding cost; Bounded total demand; Cauchy distribution; Sigmoid function